ARBITRASE SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA EKONOMI SYARIAH MENURUT UNDANG-UNDANG NOMOR 30 TAHUN 1999 - Muhibuthabary Muhibuthabary (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2014)
This paper describes the arbitration as an alternative dispute resolution in Shariah economy. Dispute resolution in general civil religion has resolved through litigation in the religious courts that refer to Article 49 of Law Number 7 of 1989 Jo. Law Number 3 of 2006 Jo. Law Number 50 of 2009 on the Religious Courts. However, there are some interesting cases, one of which is the Islamic economic disputes could be resolved through non-litigation or arbitration process, which refers to the Law No. 30 Year 1999. Now, the Shari'ah economic dispute resolution becomes the object of this study which interesting to study both theoretically and practically, not only because the case is to be part of the absolute authority of religious courts, but also becomes a new knowledge in the field of Islamic Jurisprudence